Probability assessment method and application of surface rupture on main controlling fault. Issue 3 (September 2019) - Zhang, Jianyi; Bo, Jingshan; Liu, Bideng; Huang, Jingyi
Abstract: This paper summarizes the macro-assessment of meizoseismal ground fracture experience, based on the probabilistic assessment methods described in engineering practice and research status. Earthquake engineering probabilistic analysis is the inevitable result of scientific development, to meet the people's understanding level. Statistics on the Chinese mainland strong ground fracture frequency; proposed a simple method of calculating the probability, and made a spreadsheet. The model uses data primarily from seismic hazard analysis commonly used data, the results are acceptable, the probability model is a simple, easy-to-application features.